The influence of IMF bailouts on a country’s economic development and growth - Tsoai, Konoto Queen (University of the Witwatersrand, Johannesburg, 2021)
This study investigates the influence of the IMF bailout on the country’s economic growth by evaluating the relationship the IMF bailout has with the country’s GDP, inflation, and currency exchange rate. The study reviewed the IMF operations to understand the nature of the bailout (facilities), its funding structure, and the associated conditions. The study undertook a quantitative research methodology, using panel data with cross-sectional data from five countries in the sub-Saharan region, with a time series of 20 years. Ordinary Leased Square and the Feasible Generalised Least Square were used in regressions and found that the model was a good fit for both the exchange rates and inflation but was not a good fit to model real GDP. The study found that the IMF bailout had a statistically insignificant negative relationship with real GDP, a statistically insignificant positive but weak correlation with the inflation, and a statistically significant negative relationship with the currency exchange rate. We conclude that IMF involvement in a country does not guarantee economic growth, improve the exchange rate, or help with managing inflation as promised in their purpose and objective. We recommend South Africa not to resort to the IMF bailout option and choose sovereignty over plausible atrocious IMF bailout. Instead, it must put all efforts to resolve its balance of payments issues. Should the South African government choose to opt for an IMF bailout, we recommend that they carefully consider suitable credit facilities and their conditionalities, specifically, Flexible Credit Line (FCL) and Stand-By Arrangement (SBA)
A research report presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: IMF; Bailout; Sub-Sahara; Quantitative research; Panel data; OLS; Conditionalities; UCTD; SDG-8: Decent work and economic growth